(untitled) - Yára Dadalti Fragoso; Soniza Vieira Alves-Leon; Walter Oleschko Arruda; Margarete de Jesus Carvalho; Elizabeth Regina Comini-Frota; Éber Castro Corrêa; Maria Lucia Brito Ferreira; Paulo Diniz da Gama; Sidney Gomes; Marcus Vinicius Magno Gonçalves; Damacio Ramón Kaimen-Maciel; Maria Fernanda Mendes; et al. (Arquivos de Neuro-Psiquiatria)
Objective To assess the prevalence and the profile of adverse events (AE) of natalizumab in patients with multiple sclerosis (MS). Methods Data collection from neurologists attending to patients with MS at specialized units in Brazil. Results Data from 103 patients attending the infusion centers of 16 MS units in 9 Brazilian states were included in the study. The total number of infusions was 1,042. Seventy-nine patients (76.7%) did not present any AE. Twenty-four patients (23.3%) presented only mild AE. There were three major AE, including two deaths. These three occurrences, although not necessarily being drug-related, must be taken into consideration. Conclusion The profile of AEs for natalizumab shows that 97% of patients have none or only mild AE. However, still due to safety worries, the use of this medication should be restricted to MS units under the care of specialized neurologists. Objetivo Avaliar a prevalência e o perfil dos eventos adversos (EA) por natalizumabe em pacientes com esclerose múltipla (EM). Métodos Coleta de dados fornecidos por neurologistas de unidades especializadas em EM no Brasil. Resultados No estudo, foram incluídos dados de 103 pacientes em tratamento em centros de infusão de 16 unidades de EM em 9 estados brasileiros. O número total de infusões foi 1.042. Setenta e nove pacientes (76,7%) não apresentaram nenhum EA. Vinte e quatro pacientes (23,3%) apresentaram apenas EA leves. Foram relatados três importantes EA, incluindo duas mortes. Embora não necessariamente ligadas à droga, estas EA devem ser levadas em consideração. Conclusão O perfil de EA para natalizumabe mostrou que em 97% dos pacientes não houve EA ou houve apenas EA leves. No entanto, dadas as preocupações com segurança da droga, o uso deste medicamento deve continuar restrito às unidades de EM sob os cuidados de neurologistas especializados.